An overview of 3D printing and the orthopaedic application of patient-specific models in malunion surgery. Issue 3 (March 2022) - Thomas, Claire N.; Mavrommatis, Sophia; Schroder, Lisa K.; Cole, Peter A.
Highlights: 3D models can be used to improve patient care, enhance patient and provider education, and facilitate surgical planning for complex injuries. Surgeons are uniquely positioned to utilize 3D printing and heightened awareness of the methodology of this novel technology is advantageous. Complex malunion reconstructions are distinct and require a high degree of preparation when considering intraoperative approaches. With 3D printing, innovative techniques can be increasingly incorporated into clinical workflows to allow for individualized patient care. Patients and providers both benefit from increased understanding and communication when 3D models are integrated into the planning process. Abstract: As the emerging technology of three-dimensional (3D) printing impacts several facets of medicine, innovative techniques and applications are increasingly being incorporated into clinical workflows. Specifically, 3D printing technology has allowed for the individualization of patient care through the creation of printed surgical guides, patient-specific anatomical models, and simulation practice models. In this paper, we review the broad applications of 3D printing in orthopaedic surgery. The purpose of this paper is to help orthopaedic trauma surgeons understand 3D printing's emerging influence on the delivery of care as well as how to directly apply this technology to their practice. We aim to illustrate these principles through a specific example of a patient who presented for malunion surgery. A 3D printed model of a very complex traumatic scapula malunion was used to not only pre-surgically plan the reconstruction, but to also facilitate provider and patient education. This paper highlights the benefits of 3D printing and how trauma surgeons are uniquely positioned to apply this technology to improve patient care.